Cooperative game theory : basic concepts and computational challenges - Chalkiadakis, Georgios (2013)
Cooperative game theory studies situations in which agents can benefit by working together. This article outlines the key concepts of cooperative game theory, and discusess the challenges that arise in applying these in AI applications.